Conservation Biology of Freshwater Turtles and Tortoises 2011
DOI: 10.3854/crm.5.065.pallidipectoris.v1.2011
|View full text |Cite
|
Sign up to set email alerts
|

Acanthochelys pallidipectoris (Freiberg 1945) – Chaco Side-Necked Turtle

Abstract: The Chaco Side-necked Turtle, Acanthochelys pallidipectoris (Family Chelidae), is a small to medium-sized freshwater turtle (carapace length to ca. 180 mm), endemic to the Chaco ecoregion of Argentina, Bolivia, and Paraguay. Its distribution is restricted to the temporarily flooded marshes and lowlands of dry shrub forest with impenetrable soils. The only record outside of the dry Chaco, in Mendoza, Argentina, is likely of anthropogenic origin. The activity period is very short (4-6 months a year), and populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Morphometric data revealed that A. radiolata is a small to medium-sized turtle and is the second largest species of the genus, surpassed in size only by A. macrocephala, which can reach a CL of up to 295 mm (Rhodin et al 2009). The other two species, A. spixii and A. pallidipectoris, have a maximum CL around 170 and 180 mm, respectively (Ernst & Barbour 1989;Vinke et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphometric data revealed that A. radiolata is a small to medium-sized turtle and is the second largest species of the genus, surpassed in size only by A. macrocephala, which can reach a CL of up to 295 mm (Rhodin et al 2009). The other two species, A. spixii and A. pallidipectoris, have a maximum CL around 170 and 180 mm, respectively (Ernst & Barbour 1989;Vinke et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(3) carapace and plastron scutes with radiating striations; (4) dorsal surface of the head covered with scales of irregular shape and size; (5) mesodorsal region of the head with no scales; (6) dorsal and lateral surfaces of the neck covered with small tubercles of irregular shape; (7) posterior region of the thigh with small series of tubercles (Ernst & Barbour 1989;Rhodin et al 1984b;Rhodin et al 2009;Vinke et al 2011;this study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelodiscus parviformis: Vietnam added to the range. Acanthochelys pallidipectoris: Mendoza, Argentina, corrected from native range to introduced, as per CBFTT account (Vinke et al 2011).…”
Section: Distribution Updates 2011mentioning
confidence: 99%